Cooking Method, Food Intake and Iodine Status of Pregnant Women in Saparua, Central Maluku - Intje Picauly; . Hardinsyah; Ali Khomsan; . Rimbawan (Media Gizi dan Keluarga, 2000)
The objective of this study was to analyze food intake and its cooking method in relation to iodine status of pregnant women in an endemic goitre area. For this purposes 57 pregnant women of the second trimester were selected randomly in Saparua Sub-district, an endemic goitre area of Central Maluku. Iodine status measuerd based on urinary excretion of iodine (UEI). Iodine content of urine, water, salt and common food consumed were analyzed in analytical laboratory of the Center for Research and Development of Nutrition, Bogor. The results show that stir frying, boiling, frying, boiling and frying, and grill are common cooking methods used in the study area. Lost of iodine varies depend on cooking methods and type of foods cooked. Lost of iodine content from the first two cooking method was range from 20 to 50%; and applying the last three cooking method resulted in iodine lost from 57 to74%. The iodine lost from sea fish was higher than from the other foods. The iodine food sources commonly consumed are cassava, sea fish and Ã‚Â¡Ã‚Â¥gnetumÃ‚Â¡Ã‚Â¦ (melinjo) leaves with the iodine contents 42,0-94,6 Ã†â€™ÃƒÂg/100g. The mean intake of cassava, sea fish and gnetum leaves was 559,0; 133,3 and 42,0 g/cap/day respectively. The contribution of cassava, sea fish and vegetables on iodine intake of pregnant women was 52,6; 25,4 and 18,8% respectively. All pregnant women consumed salt with the mean intake 19,2 g/cap/day and mean iodine content o,41 ppm. The mean UEI of pregnant women was 64,9 Ã†â€™ÃƒÂg/l with median 47 Ã†â€™ÃƒÂg/l. Only 17,5% of pregnant women has UEI at normal category. The result of regression analysis showed about 50% variation of UEI was explained by iodine, calcium and iron intakes (r=0,68).